Huanglongbing incidence, canopy volume, and sprouting dynamics of 'Valencia' sweet orange grafted onto 16 rootstocks - Rodrigues, Jardel D. B. [UNESP]; Moreira, Alecio S.; Stuchi, Eduardo S.; Bassanezi, Renato B.; Laranjeira, Francisco F.; Girardi, Eduardo A. (Springer, 2020)
Huanglongbing (HLB), the most important citrus disease worldwide, is associated with bacteria transmitted by the Asian citrus psyllid (ACP) preferably through new shoots present in the canopy. In a commercial citrus plant, the vegetative growth of the scion is influenced by the rootstock variety in which it is grafted. Although all commercial citrus varieties planted in recent years are susceptible to HLB, the dynamics of the rootstock in grafted plant could influence the progress of HLB, whether at the plant or grove scale. In this work, HLB incidence in 'Valencia' sweet orange grafted onto 16 rootstocks and its relationship to the tree canopy volume and flushing dynamics were evaluated in a field trial under ACP control. The experiment was conducted under rainfed conditions in Bebedouro, state of Sao Paulo, Brazil, from 2011 to 2019. 'Flying Dragon' trifoliate orange known for its dwarfing characteristics was used as the rootstock. A reduction in canopy volume by 77% at 8 years of age were observed compared to the most vigorous rootstocks. The frequency of flush shoots of 'Valencia' sweet orange was not influenced by the rootstock, but the abundance of flush shoots was lower on three semi-dwarfing rootstocks and as well as 'Flying Dragon'. Although HLB incidence on 'Flying Dragon' was lower than on 'Rangpur' lime and other three semi-standard rootstocks (trees with canopy volume between 51 and 75% of the 'Rangpur' lime canopy volume), all other combinations had similar HLB disease progress regardless of the canopy volume and flushing dynamics. Moreover, under field conditions, variations on the cumulative HLB incidence greater than 26% were necessary to significantly separate rootstocks. Therefore, the results suggest that true dwarfing rootstocks have potential to integrate the management program for HLB and that mechanisms in addition to tree vigor appear to be involved in the host-vector relationship.
Keywords: Citrus spp; Poncirus trifoliata; Candidatus Liberibacter asiaticus; Disease progress; Grafting; Tree size